Kesalahan Penyelesaian Soal Statistika Tipe High Order Thinking Skills Berdasarkan Teori Newman - Suryanti Suryanti; Candra Yunita Sari; Kristiani Kristiani (Jurnal Tadris Matematika, 2020)
In the 2013 curriculum, mathematics learning is more directed at higher-order thinking skills (HOTS). HOTS are observed from the abilities of students in solving HOTS type of questions. However, students still make mistakes in solving this type of questions, especially the statistics questions. The students’ errors in solving HOTS type of statistical questions need to be investigated, particularly on the types and causes. This study aimed to describe the errors made by students in solving HOTS type of statistical questions. This study was conducted at SMP Negeri 1 Selopuro, Blitar City Year Academic 2019/2020. This study used descriptive qualitative approach. The subjects were three students of 8th grade B. The instruments in this study were tests, interviews, and documentations. Based on the results of the data analysis, it can be concluded that: (1) reading errors were due to the inability of the students to understand the information in the questions; (2) comprehension errors were due to incomprehension of the students on what to look for in the questions; (3) transformation errors were in the form of inability in generating functions/methods to solve the questions; (4) processing skill errors were in the form of misconnection and misconception; and (5) errors in writing the final answers were due to drawing wrong conclusions.